1998
DOI: 10.1007/s000180050179
|View full text |Cite
|
Sign up to set email alerts
|

Integrins and cardiovascular disease

Abstract: Cardiovascular diseases involve abnormal cell-cell interactions leading to the development of atherosclerotic plaque, which when ruptured causes massive platelet activation and thrombus formation. Parts of a loose thrombus may detach to form an embolus, blocking circulation at a more distant point. The integrins are a family of adhesive cell receptors interacting with adhesive proteins or with counterreceptors on other cells. There is now solid evidence that the major integrin on platelets, the fibrinogen rece… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 80 publications
0
17
0
2
Order By: Relevance
“…Alterations to integrin function and/or expression is a common step in inflammation and cardiovascular disease (Clemetson and Clemetson, 1998;Hynes, 2002), and promote anchorageindependent growth, invasion and metastasis in cancer cells (Guo and Giancotti, 2004;Hood and Cheresh, 2002;Schwartz, 1997). Integrins respond to cytoplasmic signals through changes in integrinligand affinity, termed 'inside-out' signalling.…”
Section: Introductionmentioning
confidence: 99%
“…Alterations to integrin function and/or expression is a common step in inflammation and cardiovascular disease (Clemetson and Clemetson, 1998;Hynes, 2002), and promote anchorageindependent growth, invasion and metastasis in cancer cells (Guo and Giancotti, 2004;Hood and Cheresh, 2002;Schwartz, 1997). Integrins respond to cytoplasmic signals through changes in integrinligand affinity, termed 'inside-out' signalling.…”
Section: Introductionmentioning
confidence: 99%
“…Integrine sind weit verbreitete Transmembranrezeptoren, die auf vielen unterschiedlichen Zelltypen, wie EZ, GMZ, Monozyten, Leukozyten und Thrombozyten, exprimiert werden (Clemetson and Clemetson, 1998). Von den 24 bekannten Integrinen spielen 16 eine bedeutende Rolle in der vaskulären Biologie, wobei acht dieser Integrine von EZ selbst exprimiert werden (Rupp and Little, 2001).…”
Section: Leukozyten Spezifische Integrineunclassified
“…Von den 24 bekannten Integrinen spielen 16 eine bedeutende Rolle in der vaskulären Biologie, wobei acht dieser Integrine von EZ selbst exprimiert werden (Rupp and Little, 2001). Hierzu zählen die Integrine α v β 3 , α 2 β 1 , α 3 β 1 und α 5 β 1 (Luscinskas and Lawler, 1994), aber auch α 1 β 1 , α 6 β 1, α 4 β 1 und α v β 5 (Brezinschek et al, 1996;Clemetson and Clemetson, 1998;Rupp and Little, 2001 Bei der Migration bildet die Zelle in Migrationsrichtung eine Aktin-reiche Vorderseite und eine Aktin-arme Rückseite aus (Abb. 5).…”
Section: Leukozyten Spezifische Integrineunclassified
“…Studies with a 1 /a 2 integrin A domain chimeras confirmed a preference for different collagen types (Abair et al, 2008). As such, integrin receptors are central to the etiology and pathology of many diseases, such as cardiovascular (Clemetson and Clemetson, 1998), inflammatory (Apostolaki et al, 2008) and neurodegenerative disorders (Engelhardt and Kappos, 2008). They therefore have been actively targeted for drug discovery.…”
Section: Introductionmentioning
confidence: 98%